Scale validation to identify the generic strategy and organizational culture of costarican SME companies - Arce-Gutiérrez, Susan (2020)
The subject of this article is the impact of the strategy applied on SMEs in Costa Rica. The validation and adaptation of the scales based on the models of  Porter, and Cameron and Quinn were consulted, and this process constitutes the main objective of this study. Based on the review of the literature, a set of hypotheses, associated with the theories of Miles and Snow, have been raised, which were used for the validation of the convergent construct. Internal, external and construct consistency were analyzed. In order to validate content, cognitive interview was applied. On the other hand, the construct validity of Porter's strategy was verified through exploratory and convergent factorial analysis. The latter shows as a result the grouping of items according to Porter's statement. It also highlights the finding of a positive correlation between differentiation strategies and cost leadership. In addition, the scales were reliable and showed good internal consistency, except for items related to the focus strategy. This validation was made to determine if the scale can be used, in the future, to identify if company’s type of strategy and culture can influence other key aspects of SMEs in Costa Rica.